Artificial Light at Night (ALAN): A Potential Anthropogenic Component for the COVID-19 and HCoVs Outbreak - Khan, Zeeshan Ahmad; Yumnamcha, Thangal; Mondal, Gopinath; Devi, Sijagurumayum Dharmajyoti; Rajiv, Chongtham; Labala, Rajendra Kumar; Sanjita Devi, Haobijam; Chattoraj, Asamanja (Frontiers in Endocrinology, 2020)
The origin of the COVID-19 pandemic is zoonotic. The circadian day-night is the rhythmic clue to organisms for their synchronized body functions. The "development for mankind" escalated the use of Artificial Light at Night (ALAN). In this article, we tried to focus on the possible influence of this anthropogenic factor in Human Corona Viruses (HCoVs) outbreak. The relationship between the occurrences of coronavirus and the ascending curve of the night-light has also been delivered. The ALAN influences the physiology and behavior of bat, a known nocturnal natural reservoir of many Coronaviridae. The "threatened" and "endangered" status of the majority of bat species is mainly because of the destruction of their proper habit and habitat predominantly through artificial illumination. The stress exerted by ALAN leads to the impaired body functions, especially, endocrine, immune, genomic integration, and overall rhythm features of different physiological variables and behaviors in nocturnal animals. Night-light disturbs "virus-host" synchronization and may lead to mutation in the genomic part of the virus and excessive virus shedding. We also proposed some future strategies to mitigate the repercussions of ALAN and for the protection of the living system in the earth as well.